SHRINKAGE ESTIMATOR FOR A SINGLE OBSERVATION IN N(Θ,V) PROBLEM WITH UNKNOWN VARIANCE - AMER F. NASSAR (مجلة جامعة الانبار للعلوم الصرفة, 2012)
this search, Shrinkage Estimator has been studied for a Single Observation in N(θ,V) problem when variance is unknown. We proved that there is a relationship between Shrinkage Estimator and Normal Bayes Estimator. properties of this Shrinkage Estimator, Risk Function, optimal cases, Shrinkage Estimators when variance more than one, Shrinkage Estimators when variance less than one, two theorems have been put into focus